2014
DOI: 10.1074/jbc.m114.607168
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Versican in the Development of Leiomyosarcoma

Abstract: Background:The cause of leiomyosarcoma (LMS) is unknown. Results: Experimental modulation of versican levels in LMS cells resulted in altered cell proliferation, adhesion, migration, and tumor growth. Conclusion: Versican regulates the growth of LMS tumors in a mouse model. Significance: Collectively, these results suggest targeting versican in the treatment of LMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 68 publications
1
38
0
1
Order By: Relevance
“…Given that these signaling pathways regulate tumorigenesis and that V3 expression in melanoma cells has been shown to significantly reduce tumorigenesis (16 -18), V3 may negatively impact tumorigenesis by affecting Wnt/␤-catenin and Notch signaling pathways. Recently, we have also found that negatively regulating versican in leiomyosarcoma cells significantly blocked tumorigenic potential when subcutaneously implanted into nude mice (53), which suggests V3 as a negative regulator of larger isoforms of versican may provide a novel anti-tumorigenic approach. A, changes in C3, Ccl2, Cxcl1, Ccl20, and Cxcl5 transcript levels were validated by qPCR using control LXSN or V3-expressing ASMCs cultured for 10 days.…”
Section: Discussionmentioning
confidence: 94%
“…Given that these signaling pathways regulate tumorigenesis and that V3 expression in melanoma cells has been shown to significantly reduce tumorigenesis (16 -18), V3 may negatively impact tumorigenesis by affecting Wnt/␤-catenin and Notch signaling pathways. Recently, we have also found that negatively regulating versican in leiomyosarcoma cells significantly blocked tumorigenic potential when subcutaneously implanted into nude mice (53), which suggests V3 as a negative regulator of larger isoforms of versican may provide a novel anti-tumorigenic approach. A, changes in C3, Ccl2, Cxcl1, Ccl20, and Cxcl5 transcript levels were validated by qPCR using control LXSN or V3-expressing ASMCs cultured for 10 days.…”
Section: Discussionmentioning
confidence: 94%
“…Versican expressed by some tumor cells affects their growth and metastatic potential. For example, versican is highly expressed in sporadic clear cell renal cell carcinoma inhibiting cell death [43] and in sarcomas promoting tumor cell proliferation and migration and increasing HA production [44, 45]. Abrogation of versican expression in T-anaplastic large cell lymphoma results in decreased levels of membrane type 1-MMP (MT1-MMP) and CD44 and marked suppression of T-cell adhesion and invasion [46].…”
Section: Versican: a Tumor Stroma-associated Proteoglycan In Breasmentioning
confidence: 99%
“…In previous studies [32], LMS cells were treated with individual in vitro transcribed siRNAs specifically directed and spaced along the length of versican mRNA. Quantitative Real Time-Polymerase Chain Reaction (qRT-PCR) mRNA analyses revealed that the 5´-G1-directed siRNA was the most effective at inhibiting versican.…”
Section: Resultsmentioning
confidence: 99%
“…Leiomyosarcoma (LMS) cells, for example, produce a large amount of versican and, in previous experiments, we have shown that inhibiting versican synthesis in LMS cells inhibits both proliferation and tumor formation when these cells are injected into nude mice [32]. Correspondingly, we have found that the addition of exogenous versican restores the high proliferative rate of slow proliferating versican-depleted LMS cells while increasing migration and decreasing substrate adhesion [32]. …”
Section: Introductionmentioning
confidence: 99%